THE IMPORTANCE OF CONTINUITY AND CONTINUITY IN TECHNOLOGY SCIENCE IN GENERAL SECONDARY SCHOOLS (American Journal of Technology and Applied Sciences, 2023)
In the direction of modern technology in existing educational institutions, the fact that the quality of training of teacher educators and staff does not correspond to the requirements of today assumes a radical revision of the teaching of technology and updating it in accordance with the requirements of the period. And for this, it is necessary to understand the content and essence of continuity and continuity in the science of technology in general secondary education schools.